PROSES HUKUM PERKAWINAN ADAT BALI DENGAN PENDEKATAN ILMU FILOLOGI - Subrata, I Nyoman (VYAVAHARA DUTA, 2020)
Marriage is based on a desire to build a family order and hereditary system. In the procedure of marriage is supported on the basis of the approval of the Balinese Customary party as well as the law that has been in force in the State of Indonesia. The Balinese Traditional Marriage Process embraced by the Balinese community is approved by the national and indigenous marriage law. In marriage, there will be an approach process with Philology as a reference or guideline on every balinese customary marriage activity as well as the Marriage Law that has been in effect in every region of Indonesia. This includes on the basis of an Indigenous Marriage in Bali with the legal process that has been in effect and followed by the reference approach of Philology Science.Â Keywords : Marriage Law, Balinese Customs, Philology